Effect of Operating Temperature on Performance of Obliquely Deposited Bi, Sb and Bi-Sb Semimetal Thin Film Laser Detectors - Ismail, Raid A.; Hamudi, Walid K.; Al-Makadusi, Afnan K. (Iraqi Journal of Laser, 2004)
Obliquely deposited (70o) Bi, Sb, and Bi-Sb alloy thin films have been prepared by thermal resistive technique. Structural properties of these films were studied using XRD. Their resistance and voltage responsivity for Nd:YAG and CO2 laser pulses have been recorded as function of operating temperature between 10 oC and 120 oC. It was found that the maximum responsivity for these detectors can be obtained at 75 oC. On the other hand, the dependence of responsivity on the width of detectors was investigated.